2022
DOI: 10.35409/ijbmer.2022.3367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transformational Leadership on Employee Performance and Organizational Performance Mediated by Job Satisfaction and Organizational Commitment of Banda Aceh PLN Customer Service Implementation Unit

Abstract: This study aims to measure the effect of transformational leadership on employee performance and organizational performance mediated by job satisfaction and organizational commitment. This study was conducted at the State Electricity Company (PLN), in the customer service implementation unit (UP3) at Banda Aceh (PLN UP3 Banda Aceh). The research population was 150 people, where the entire population was a permanent employee and has worked for more than 3 years. The Census method was used to determine the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This explains the better the leadership style the higher organizational performance. Referring to research conducted by (Warahmah, Harmen and Kesuma, 2022) is in line with this study finding that leadership style influences organizational performance. (Salmi, Adam and Nizam, 2022) in their research also stated that leadership style directly affects organizational performance.…”
Section: H5: Leadership Style On Organizational Performancesupporting
confidence: 88%
“…This explains the better the leadership style the higher organizational performance. Referring to research conducted by (Warahmah, Harmen and Kesuma, 2022) is in line with this study finding that leadership style influences organizational performance. (Salmi, Adam and Nizam, 2022) in their research also stated that leadership style directly affects organizational performance.…”
Section: H5: Leadership Style On Organizational Performancesupporting
confidence: 88%
“…The indirect test results found that career commitment fully mediates the effect of public service motivation on organizational performance, and career commitment partially mediates the effect of job satisfaction on the performance of the organization. (Warahmah et al, 2022) concluded that organizational leadership influences positively and significantly job satisfaction, career commitment, employee performance, and organizational performance.…”
Section: H8: Career Commitment Role In Bas-oho Employee Performancementioning
confidence: 99%